Empirical insights into traditional and AI-enhanced interactive narratives based on children’s fables - Świerczyńska-Kaczor Urszula (Journal of Economics and Management)
Aim/purpose – The study delves into the creation and the experience of interactive children’s narratives based on poetry, examining the emerging role of artificial intelligence (AI) as a collaborative partner in storytelling for children. The research questions are: 1) What are the experiences of readers, specifically children’s guardians, with interactive narratives based on children’s poetry?; 2) How do children’s guardians experience inter-active stories co-generated in real-time through conversations with artificial intelligence?; 3) Is it feasible to create a satisfying narrative for children from a specific set of images through the use of AI technology?